2005
DOI: 10.1111/j.1444-2906.2005.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Water quality fluctuations under floating net cages for fish culture in Lake Cirata and its impact on fish survival

Abstract: Vertical profiles of water quality were surveyed before and after mass mortality of fish cultured in cages in Lake Cirata, a man made lake in Indonesia. The first survey was performed 4 months before the mass mortality and the second survey was carried out 4 days after the mass mortality. In the first survey, the conditions below 8 m depth were reductive and anoxic, although at 8 and 10 m depth, the water became oxidative in spite of low oxygen concentration in the second survey. These changes were probably ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…It is different from the lakes and reservoirs in temperate areas. Effendie et al (2005) pointed out that the massive fish kill in the Cirata Reservoir was caused by a reductive condition derived from the deeper layer by strong vertical mixing. They observed an unstable temperature profile and a high concentration of ammonia in the surface layer 4 days after a massive fish kill in December 2000.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is different from the lakes and reservoirs in temperate areas. Effendie et al (2005) pointed out that the massive fish kill in the Cirata Reservoir was caused by a reductive condition derived from the deeper layer by strong vertical mixing. They observed an unstable temperature profile and a high concentration of ammonia in the surface layer 4 days after a massive fish kill in December 2000.…”
Section: Resultsmentioning
confidence: 97%
“…In this reservoir, massive fish kills have occasionally occurred in the fish culture lately (Garno 2002;Abery et al 2005;Effendie et al 2005). Garno (2002) pointed out that degradation of the water quality caused by increasing organic waste from the fish culture would generate this problem.…”
Section: Introductionmentioning
confidence: 97%
“…Freshwater aquaculture is a key activity in commercial fisheries in Indonesia, with the related products being an important source of protein for many people, especially those who live in urban areas (Effendie et al 2005). Food and Agriculture Organization (FAO) aquaculture statistics also confirmed that Indonesia produced a great many fish types to meet both domestic demand and export needs with the highest rank of fish types being Common carp (67.95 %), Nile tilapia (24.56 %), and Giant gourami (2.09 %), among others.…”
Section: Selection Of Fish Typesmentioning
confidence: 99%
“…This may be due to poor water quality leading to more frequent or severe outbreaks of koi herpes virus disease (KHVD) (Abery et al 2005), as well as water quality parameters exceeding the physiological tolerances of the carp. In Cirata reservoir, West Java, there have been several reported mass fish kills due to degraded water quality (Effendie et al 2005;Phillips & De Silva 2006;Hayami et al 2008;Edwards 2010). During the last turnover of the reservoir's water in 2007, there was an 80% mortality of all species (Edwards 2010).…”
Section: Environmentalmentioning
confidence: 99%
“…During the last turnover of the reservoir's water in 2007, there was an 80% mortality of all species (Edwards 2010). The Cirata fish kills appear to be caused by mixing of the lower anoxic layer waters, which begin at only 7-8 m depth (Effendie et al 2005;Phillips & De Silva 2006;Hayami et al 2008). Because of the shallow oxycline in Cirata reservoir (7-8 m depth), even moderate mixing due to wind-induced upwelling or vertical mixing can result in massive fish kills (Hayami et al 2008).…”
Section: Environmentalmentioning
confidence: 99%